Atividade reprodutiva dos peixes do rio Macaé (RJ) em função do gradiente longitudinal - Brito, Marcelo Fulgêncio Guedes de (2007)
The reproductive activity of fishes was evaluated relative to the phisiographic (altitude) and abiotic (conductivity, water temperature, disolved oxigen and rainfall) parameters throughout the longitudinal gradient of Macaé River (RJ). Sampling was carried out in twelve sites, four in each of the three river stretches (upper, intermediate and lower) from March/2004 to March/2005. Higher densities of larval stages was found in marginal areas, using two distinct methods (hand sieve in marginal vegetation, and plankton net in drift in river channel) in order to sample eggs, larvae and juveniles. A positive correlation was observed between densities of both larvae and juveniles in marginal vegetation and rainfall records. Larvae and juveniles in the drift had higher densities in November, but no correlation between densities and rainfall values was recorded. Eggs occurred in low densities using both sampling methods. Sampling of initial development forms in the marginal vegetation was performed with equipment designed for this study, which has shown great efficiency. The case study of catfish Neoplecostomus microps demonstrated differences in the distribution pattern according to age structure. Larvae have shown to be dependent on the marginal vegetation during early life history stages, where shelter is provided right after hatching. Juveniles remain for a short period in marginal sites, and later swim towards the river channel where they remain during the whole adult stage. Reproductive sites were for this species were found under boulders in riffles in Macaé River and Boa Esperança River. Sexual dimorphism was apparent as differences in urogenital papilae, and presence of prominent epidermal projection on the pectoral fin of males. Both the sexual dimorphism and reproductive site represent unpublished records to genera. Differences in reproductive patterns among the seven Loricariidae species, allowed us to separate species into three distinct groups: (i) species that inhabit riffles in the river channel and have the recruitment during a short period associated to rainfall (N. microps and H. punctatus); (ii) species that inhabit the intermediate stretch and have recruitment throughout the year or at least during the most part of the year, and reproductive investment also over a large period (Rineloricaria sp. 1, Rineloricaria sp. 2 e S. guntheri); and (iii) floodplain species with recruitment throughout the year and increase in reproductive activity during the rainy period (H. notatus e P. maculicauda). Floodplain species were found to have lower recruitment in the channellized strecht of river relative to the natural strecht, which might possibly be related to this anthropic alteration. For the other species, seasonality might be regarded as an important factor that triggers the reproductive process. One group has shown to have a long reproductive period, as a strategy to guarantee population replacement, as species inhabit sites exposed to unpredictable events that might disrupt the habitats. The other group exhibits has a short to intermediate reproductive period, with most species reproducing during the rainy season, when ecosystem productivity is highest. We propose reproductive guilds established according to the reproductive styles of species (nonguarders, guarders and bearers).